Front Cover: Nitrogen Disturbance Awakening the Intrinsic Activity of Nickel Phosphide for Boosted Hydrogen Evolution Reaction (ChemSusChem 16/2022). Issue 16 (1st August 2022) - Yang, Caixia; Wang, Zhiqiang; Li, Zhendong; Pan, Yichen; Jiang, Linwei; Li, Caicai; Wang, Chao; Sun, Qingfeng
Abstract : The Front Cover shows that N‐doping enhances electrocatalytic activity of Ni2 P for green H2 generation. More information can be found in the Research Article by C. Yang, Z. Wang, et al .